2006
DOI: 10.1158/1055-9965.epi-06-0005
|View full text |Cite
|
Sign up to set email alerts
|

Serum Heat Shock Protein 70 Levels and Lung Cancer Risk: A Case-Control Study Nested in a Large Cohort Study

Abstract: Chronic inflammation contributes to the process of carcinogenesis, but few epidemiologic studies have examined associations with risk of lung cancer. Relationships between lung cancer risk and serum levels of both heat shock protein 70 (Hsp70) and high-sensitivity C-reactive protein (hsCRP) were investigated in a case-control study nested in the Japan Collaborative Cohort Study for Evaluation of Cancer Risk. Serum samples and lifestyle information were collected at baseline from 39,242 men and women between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…The sex effect in extended HLA complex associations with childhood ALL has already been reported by us and others (Taylor et al 1998;Dorak et al 1999a, b;Ng et al 2006). Notably, the positive correlation between high HSP serum levels and lung cancer susceptibility is also observed in males only (Suzuki et al 2006). We did not have serum samples from our cases and controls to examine associations with serum levels in childhood ALL.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The sex effect in extended HLA complex associations with childhood ALL has already been reported by us and others (Taylor et al 1998;Dorak et al 1999a, b;Ng et al 2006). Notably, the positive correlation between high HSP serum levels and lung cancer susceptibility is also observed in males only (Suzuki et al 2006). We did not have serum samples from our cases and controls to examine associations with serum levels in childhood ALL.…”
Section: Discussionsupporting
confidence: 65%
“…Due to the strong haplotypic relationships between HSP70 gene polymorphisms and HLA haplotypes (Favatier et al 1997;Dorak et al 2006), HSP70 polymorphisms may even account for some of the HLA associations observed in cancers. An association between higher HSP70 serum levels and increased lung cancer risk has been reported but in males only (Suzuki et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer patients, serum HSP70 level was found significantly increased and it could be useful as an additional biomarker for the detection of pancreatic cancer (Dutta et al 2012). Also serum HSP70 has been shown as an indicator for high mortality in patients with colorectal cancer and its serum levels has been shown to predict increased risk of lung cancer (Suzuki et al 2006;Kocsis et al 2011). Based on these studies we intended to determine the serum levels of HSP70 in BC patients.…”
Section: Al 2010)mentioning
confidence: 99%
“…In recent studies, serum HSP70 has been shown as a biomarker for early detection of pancreatic cancer (Dutta et al 2012) and as an indicator for high mortality in patients with colorectal cancer without distant metastasis (Kocsis et al 2011). In addition, its elevated serum levels were associated with increased risk of lung cancer (Suzuki et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CRP is synthesized by the liver in response to factors released by macrophages and fat cells (adipocyte) [17]. Many studies have shown that CRP has been implicated in the process of carcinogenesis [18,19]. Several metabolic changes occur in cancer development, and electrolyte imbalance is one of them.…”
Section: Introductionmentioning
confidence: 99%